2018
DOI: 10.3389/fpsyt.2018.00447
|View full text |Cite
|
Sign up to set email alerts
|

Dose Reduction/Discontinuation of Antipsychotic Drugs in Psychosis; Effect on Cognition and Functional Outcomes

Abstract: Backgrounds: There is a debate regarding the optimal timing of discontinuation of antipsychotic drugs in patients with first episode psychosis (FEP) or schizophrenia. We aimed to provide a review of the literature on which strategy (medication maintenance vs. dose reduction/discontinuation) is more likely to maximize outcomes, such as cognition and social function.Methods: Using PubMed, the Cochrane Library and systematic reviews, articles published between 2007 and 2018 were reviewed, which investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The fact that cognitive impairment is evident at first-episode schizophrenia and in individuals who have a genetic or clinical high-risk for developing schizophrenia further supports this notion (Mesholam-Gately et al ., 2009; Agnew-Blais and Seidman, 2013; De Herdt et al ., 2013; Bora et al ., 2014; Bora and Pantelis, 2015). However, other factors such as metabolic syndrome, alcohol use, chronic stress and antipsychotics can also contribute to cognitive impairment in schizophrenia (Potvin et al ., 2008; Thoma and Daum, 2013; Sahu et al ., 2016; Bora et al ., 2017 b ; Omachi and Sumiyoshi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that cognitive impairment is evident at first-episode schizophrenia and in individuals who have a genetic or clinical high-risk for developing schizophrenia further supports this notion (Mesholam-Gately et al ., 2009; Agnew-Blais and Seidman, 2013; De Herdt et al ., 2013; Bora et al ., 2014; Bora and Pantelis, 2015). However, other factors such as metabolic syndrome, alcohol use, chronic stress and antipsychotics can also contribute to cognitive impairment in schizophrenia (Potvin et al ., 2008; Thoma and Daum, 2013; Sahu et al ., 2016; Bora et al ., 2017 b ; Omachi and Sumiyoshi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The present data also converge with emerging findings of drug effects on cognition in first‐episode bipolar disorder and first‐episode psychosis more broadly. Based on a recent review investigating the effects of either tapering/withdrawing or maintaining antipsychotic treatments in remitted first‐episode psychosis patients, Omachi & Sumiyoshi reported that patients who discontinued such treatments showed better cognitive outcomes than those who were maintained on antipsychotic treatments. In our initial 1‐year longitudinal study, we also reported better one‐year cognitive outcomes in executive functioning in patients who discontinued antipsychotic treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The possibility has been raised that a proportion of patients whose first-episode has remitted may be candidates for discontinuation of antipsychotic medication in the medium to long term, at least within the context of a specialist first-episode service providing effective psychosocial interventions (Alvarez-Jimenez et al, 2016). According to such a view, the possible advantages for such patients might be the avoidance of adverse effects, improvement of the therapeutic relationship and better cognitive and social function (Omachi and Sumiyoshi, 2018; Wunderink et al, 2013). Relevant to such a view are the results of the MESIFOS study (Wunderink et al, 2007), which looked at outcomes for people with remitted first-episode, non-affective psychosis, who had been assigned to either continuing antipsychotic medication or a guided reduction in dosage, with withdrawal if achievable.…”
Section: First-episode Psychosismentioning
confidence: 99%